ENGLISH KEREN REK (EKR) WEB BASE GAME APPLICATION MODEL TO ENRICH X GRADE STUDENTS’ ENGLISH GRAMMAR ACHIEVEMENT - Hestiningrum Yunita Sari Putri; Supriyono Supriyono; Aini Miza Rahmatika (JOSAR (Journal of Students Academic Research), 2019)
This research was aimed at establishing, describing the implementation, and finding out the influence of the English Keren Rek (EKR) Web Base Game Application Model. This research applied Qualitative and Quantitative approches with Research and Development Design by using adapted Sugiyono’s Model. This research consisted of three phases, which were first: foundational research to identify potencies and problems; second: design and development research; and third: experimental research. The valid final model contained of opening, home display, games display, learning materials, and evaluation. The validation score of overall model components was 77.75% which meant very propper. The tests validity and reliability values were (0.999) by alpa Corn-batch and (0.999) by using split half technique. The one-group pre and post test experimental research showed that before using the model, the average students’ achievement was (51) and after using the model it reached (85.05) by which the students gained (34.05) which meant 60% increase of the mean score. Having the value of t-test with tcount -35.556 < ttabel 2.03011 by Significant value of 0.05, this showed that the model positively influenced the students’ grammar achievement. The implementation turned out to be interesting and motivating.